P032: Identifying the bleeding and thrombosis learning needs of the Free Open Access Medical education (FOAM) community. (15th May 2017) - Chan, T.M.; Jo, D.; Candidate, MD; Shih, A.; Bhagirath, V.; Yeh, C.; Castellucci, L.; Thoma, B.; de Wit, K.
Abstract : Introduction: Developing structured online educational curricula that meet learner needs is challenging. Thrombosis and bleeding are areas of innovation and change in emergency medicine. We aimed to determine the learning needs of the Free Open Access Medical education (FOAM) community with the subsequent goal of developing structured curricula to meet them.Methods: A Massive Online Needs Assessment (MONA) was conducted to determine the perceived and unperceived educational needs in thrombosis and bleeding. The survey was designed by a multidisciplinary team of experts and was open from September 20 to December 10, 2016. The survey requested limited demographic information and contained questions to identify topics of interest. Respondents' baseline knowledge and unperceived needs were assessed using 5 case scenarios containing 3 questions each. Knowledge gaps were defined a priori as topics where <50% of participants answered correctly.Results: We received 198 complete responses by staff physicians (n=109), residents (n=46), medical students (n=29) and allied health professionals (n=14) from 20 countries. 116/198 responses were from people working in emergency medicine. Topics of interest to participants included choice of anticoagulants, interruption of anticoagulation, management of bleeding and monitoring anticoagulation. Knowledge gaps were identified in 4 main areas including interruption of anticoagulation, management of bleeding (including reversal of anticoagulation and massive transfusion), inherited thrombophilia, and screening for malignancy in acute thrombosis.Conclusion: We have identified six priority topics to cover in our future online Thrombosis and Bleeding curriculum by surveying the online medical community. Although perceived and unperceived needs showed high congruence, two priority topics were only identified by assessing unperceived needs.